EVALUATION OF THE PERFORMANCE OF A 3-PHASE INDUCTION MOTOR IN A COOLING TOWER SYSTEM AT PT. POLYCHEM INDONESIA TBK - Qonita Auliani; Bagus Dwicahyono (TESLA: Jurnal Teknik Elektro, 2025)
This study aims to evaluate the performance of three-phase induction motors used in cooling tower systems at PT. Polychem Indonesia Tbk. Cooling towers play an important role in maintaining production stability in the chemical industry, where motor reliability is essential to ensure continuous water circulation. This study uses a quantitative approach through an online inspection method with the main parameters measured including voltage, current, and temperature. Field observations are supplemented with literature studies and interviews with experienced technicians to strengthen the analysis. The measurement results show that the motor operates within safe limits, with voltage maintained stable below 400 V, current not exceeding the nominal current of 345 A, and operating temperature remaining below 75°C. Error analysis shows a relatively small average error percentage, namely 0.02% for voltage, 0.05% for temperature, and 0.16% for current. These values are well below the ±5% tolerance limit according to the IEC 13B-23 standard, thus proving the accuracy of the measurements and the reliability of the motor's performance. These findings also indicate that a routine preventive maintenance program can minimize the risk of overvoltage, overcurrent, and overheating. Thus, it can be concluded that the GM-315 A three-phase induction motor is still operating reliably, efficiently, and safely in supporting the cooling tower system at PT. Polychem Indonesia Tbk Abstrak Penelitian ini bertujuan untuk mengevaluasi kinerja motor induksi 3 fasa yang digunakan pada sistem cooling tower di PT. Polychem Indonesia Tbk. Cooling tower berperan penting dalam menjaga kestabilan produksi pada industri kimia, di mana keandalan motor sangat dibutuhkan untuk memastikan sirkulasi air berjalan kontinu. Penelitian ini menggunakan pendekatan kuantitatif melui metode on-line inspection dengan parameter utama yang diukur meliputi tegangan, arus, dan suhu. Observasi lapangan dilengkapi dengan studi literatur serta wawancara dengan teknisi berpengalaman guna memperkuat analisis. Hasil pengukuran menunjukkan bahwa motor beroperasi dalam batas aman, dengan tegangan terjaga stabil di bawah 400 V, arus tidak melebihi arus nominal 345 A, dan suhu operasional tetap berada di bawah 75°C. analisis error menunjukkan nilai rata-rata persentase error yang relatif kecil, yaitu 0,02% untuk tegangan, 0,05% untuk suhu, dan 0,16% untuk arus. Nilai ini jauh di bawah batas toleransi ±5% sesuai standar IEC 13B-23, sehingga membuktikan tingkat akurasi pengukuran serta keandalan kinerja motor. Temuan ini juga mengindikasikan bahwa program pemeliharaan preventif yang dilakukan secara rutin mampu meminimalkan risiko terjadinya overvoltage, overcurrent, maupun overheating. Dengan demikian, motor induksi 3 fasa GM-315 A dapat disimpulkan masih bekerja dengan andal, efisien, dan aman dalam mendukung sistem cooling tower di PT. Polychem Indonesia Tbk